Questionnaire construction of deviant sexual behavior and awareness on sexual deviation behaviour. - Ahmad, Roslee; Jusoff, Kamaruzaman; Mustaffa, Mohamed Sharif; Jusoh, Ahmad Jazimin (2011)
The purpose of this paper is to discuss the process of developing Questionnaires of DeviantSexual Behavior and Awareness on Sexual Deviation Behavior Based on Islam. Somecriteria’s has been identified to develop these questionnaires in the aspect of psychology,counseling and Islamic education. The benefit is to produce an applicable instrument to theIslamic context. These questionnaires were developed through integrated discipline of psychology, counseling and Islam and the aim is for enable to measure sexual deviantbehavior from the Islamic perspective. The main sources of these references were based on Diagnostic and Statistical Manual of Mental Disorders Text Revision (2000), Checklist Sexual Behavior Inventory (Friedrich, 1997), Al Ghazali Model (Yatimah and MohdTajudin, 2008) and the tendency of immoral behavior based on human sense according toIslam (Amir Hassan, 2007). DSM-IV-TR (2000) which involved some clinical items such as exhibitionism, frotteurism and voyeurism. Meanwhile Checklist Sexual Behaviour Inventory (Friedrich, 1997) were refers to personal boundaries, exhibitionism, self-stimulation, sexualinterest, sexual knowledge and voyeuristic behavior. Counseling Model Based On HumanTraits Al Ghazali (Yatimah and Mohd Tajudin, 2008) involved some items such aslimitation in intermingle, aurat limitation, sense limitation, and the tendency of immoralbehaviour based on human sense according to Islam (Amir Hassan, 2007) such as part of body, hands, mouth, ear and eye. These questionnaires has been evaluated for the contentvalidity and expert validity from the internal expert and external expert. The result of thesequestionnaires showed a commonly acceptable for the Cronbach alpha value more than 0.6(Kerlinger, 1979). The Questionaires of Deviant Sexual Behaviour Based on Islam for thevalue of Cronbach Alpha was 0.7038 and Awareness on Sexual Deviation Behaviour Based on Islam for the Cronbach Alpha was 0.7183.